Food habits of harbor seals (Phoca vitulina richardii) as an indicator of invasive species in San Francisco Bay, California. Issue 3 (2nd April 2015) - Gibble, Corinne M.; Harvey, James T.
Abstract The diet of harbor seals (Phoca vitulina richardii) in San Francisco Bay (SFB), California, was determined from July 2007 to July 2008 using prey hard parts recovered from 442 scats collected at five haul‐out sites. Twenty‐two species of fish and one species of crustacean were identified, but harbor seals primarily ate a nonnative invasive species, yellowfin goby (Acanthogobius flavimanus), which increased in dietary importance since the diet was last studied in 1991/1992. Additionally, another nonnative invasive fish species, chameleon goby (Tridentiger trigonocephalus), was found for the first time in the diet of harbor seals in SFB. Harbor seal diet was statistically different between years (1991/1992 and 2007/2008), between the pupping and nonpupping seasons, and between North SFB and South SFB haul‐out locations. The diet of harbor seals was significantly correlated with fish species caught in trawl surveys conducted by the California Department of Fish and Wildlife (CDFW) during the same time periods as this study (2007/2008). Harbor seals currently are influencing the health of the SFB ecosystem in a positive manner by consuming large quantities of nonnative invasive fish species.